Nutrition and Food Practices in Italian Older Population’s Care Facilities: An In-Depth Analysis of Public Guidelines and Recommendations - Pagliarino, Elena; Autiero, Annachiara; Ciappelloni, Lucrezia; Pecoraro, Fabrizio (Italian Sociological Review, 2026)
Sociodemographic projections of population aging, healthy life expectancy, and household composition depict a future with an increasing number of older individuals living alone and in need of care. Older population’s care facilities play a crucial role in promoting healthy aging, and within these facilities, nutritional and dietary practices complement care and prevention measures. The World Health Organization and the Italian National Institute of Health emphasize the importance of establishing long-term care standards and resources informed by scientific evidence to guide interventions. This study seeks to advance knowledge and improve practices by examining existing public guidelines and recommendations concerning food services in Italian older population’s care homes. Documents were collected via Google’s search engine using the keywords ‘guidelines’ or ‘recommendations’ in combination with ‘collective catering for older people’, ‘hospital catering’, ‘healthcare catering’, and ‘social care catering’. Documents were analyzed via a thematic framework defined by the research team, which was designed to identify common recommendations, differences, and innovative elements in key strategic areas of intervention. 35 documents addressing various aspects of elderly dining, including optimal nutrition, suitable diets, best practices to enhance the quality and effectiveness of food provision and consumption, and the monitoring of guideline implementation, were analyzed. The analysis was performed via qualitative software (MAXQDA24). The study concludes that there is a proliferation of guidelines with little coordination between them. While the Mediterranean Diet is cited as the reference model, this appears more rhetorical than substantial. Furthermore, the lack of a robust monitoring system to oversee the implementation of these guidelines risks undermining their effectiveness.